2018
DOI: 10.14744/anatoljcardiol.2017.7839
|View full text |Cite
|
Sign up to set email alerts
|

Aortic ⍺-smooth muscle actin expressions in aortic disorders and coronary artery disease: An immunohistochemical study

Abstract: Objective:The is to report immunohistochemical observations of aortic α-smooth muscle actin (SMA) expressions in patients with aortic aneurysm, acute aortic dissection, and coronary artery disease and to discuss phenotypic switching of smooth muscle cells (SMCs) of these lesions.Methods:Forty-nine consecutive patients scheduled for surgical treatment for acute type A aortic dissection (20 patients), aortic aneurysm (9 patients), and coronary artery disease (20 patients) were included. Surgical specimens of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Lack of α-SMA positive cells in the middle layer of the aortic wall in patients with AAA was observed in comparison to control cells of aorta (Lesiak et al unpublished work). α-SMA expressions in aortic smooth muscle cells of patients with AAA were significantly reduced (Yuan and Wu 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Lack of α-SMA positive cells in the middle layer of the aortic wall in patients with AAA was observed in comparison to control cells of aorta (Lesiak et al unpublished work). α-SMA expressions in aortic smooth muscle cells of patients with AAA were significantly reduced (Yuan and Wu 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Mean ± SD 3 ± 3 2.1 ± 1.6 3.9 ± 5.3 4.9 ± 3.9 3.7 ± 4.4 4 ± 6.1 3.5 ± 2.9 2.7 ± 1.6 8.7 ± 1 Cells that were obtained from patients with AAA were analyzed for their phenotypes using flow cytometry and markers specific for the particular expected types of cells. The markers used in our work were selected based on reports by numerous authors who have demonstrated results of immunohistochemical analyses of the aortic wall, showing these specific cells in different parts of the aorta [12][13][14]. Flow cytometry data of cells from the IL of AAAs showed that these cells did not show CD31 or vWF antigens.…”
Section: Cd68mentioning
confidence: 99%
“…In a normal individual, VSMCs of the aorta demonstrate a well-differentiated, contractile state; in atherosclerosis, the VSMCs expressed increased amount of the ⍺-smooth muscle actin (SMA) indicating a shift toward the synthetic phenotype leading to a narrowing in the lumen. In patients with aortic aneurysms, VSMCs expressed decreased amount of the ⍺-smooth muscle actin (SMA) indicating a severe SMC degeneration or a switch between the contractile and synthetic phenotype of SMCs, which may be even bene icial because of the production of an extracellular matrix that is necessary for healing of the vascular wall [23].…”
Section: Pathogenesismentioning
confidence: 99%